2013
DOI: 10.1152/ajpheart.00714.2012
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epicatechin administration and exercising skeletal muscle vascular control and microvascular oxygenation in healthy rats

Abstract: Consumption of the dietary flavanol (-)-epicatechin (EPI) is associated with enhanced endothelial function and augmented skeletal muscle capillarity and mitochondrial volume density. The potential for EPI to improve peripheral vascular function and muscle oxygenation during exercise is unknown. We tested the hypothesis that EPI administration in healthy rats would improve treadmill exercise performance secondary to elevated skeletal muscle blood flow and vascular conductance [VC, blood flow/mean arterial press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…These results agree with most of the human studies considering cocoa polyphenols [28]. With regard to preclinical studies, the available evidence is quite controversial: some studies reported improvements [7,52,53], and others revealed no changes [8] or even a decrease in exercise performance after dietary interventions with cocoa or its isolated polyphenols [54]. Future studies may clarify how the antioxidant properties of cocoa and cocoa fiber, by means of preventing the overproduction of ROS, affect exercise performance in a chronic manner.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results agree with most of the human studies considering cocoa polyphenols [28]. With regard to preclinical studies, the available evidence is quite controversial: some studies reported improvements [7,52,53], and others revealed no changes [8] or even a decrease in exercise performance after dietary interventions with cocoa or its isolated polyphenols [54]. Future studies may clarify how the antioxidant properties of cocoa and cocoa fiber, by means of preventing the overproduction of ROS, affect exercise performance in a chronic manner.…”
Section: Discussionsupporting
confidence: 84%
“…The predominant catechin monomer found in cocoa is (-)-epicatechin [6], and given its high abundance, it is believed that it could play an essential role in the beneficial effects of cocoa. For this reason, several authors have focused their attention on the isolated effect of this catechin on exercise performance [7], muscle oxygenation [8], and cytokine production [9], among others [10]. However, it is important to consider that cocoa also contains other bioactive compounds, such as dietary fiber and methylxanthines, which may contribute to cocoa's beneficial effects on health and particularly on the immune system [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on exercise performance, the cocoa diet did not improve it, which agrees with most of the human studies using cocoa polyphenols ( 25 ). Even so, some preclinical studies have reported that (–)-epicatechin and (–)-epicatechingallate, both flavanols present in cocoa, exert ergogenic effects in rodents ( 41 43 ), while others reported no changes ( 44 ) or even a decrease in time-to-exhaustion after a 6-month dietary intervention ( 45 ). The controversy in these results may be due to the dosage of cocoa or its polyphenol content, as well as the exercise protocol applied.…”
Section: Discussionmentioning
confidence: 99%
“…Treadmill exercise capacity has been assessed in animal models of heart failure (48, 49), diabetes (50), aging (51,52) and skeletal muscle pathophysiology (53)(54)(55)(56). Motorised rodent treadmills have been used in sepsis models though as a means of determining the impact of endurance training on outcomes (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%